Analysis of Corruption Crimes in Government Institutions - Siti Nurjannah Lase; Zahara Ananda; Amanda Putri Fajrin; Taufik Hidayat Batubara (Jurnal Sahabat ISNU SU, 2025)
Corruption in government institutions is no longer a new problem in Indonesia, in fact it can be said that corruption has become a deviant culture to gain wealth and personal gain using public or state funds illegally by abusing power or authority. The purpose of this paper is to analyze criminal acts of corruption in government institutions, determine the impact of criminal acts of corruption in government institutions, and efforts to minimize criminal acts of corruption in government institutions. The writing method used is normative legal research, descriptive, library research or literature review by reviewing published literature relevant to the problem studied. The results of this study indicate that criminal acts of corruption are a very significant problem because they can hinder economic growth and national development, therefore serious action is needed to overcome or minimize them. Efforts that can be made to eradicate criminal acts of corruption in government institutions are increasing transparency related to budget management in government institutions and increasing prison sentences for corruptors, which are expected to reduce criminal acts of corruption.